Evaluasi Penerapan Prinsip Arsitektur Berkelanjutan dan Healing Environment pada Gedung Rawat Inap RSUD Ulin Banjarmasin - Tirtana, Dedy; Rahman, Akbar; Febrita, Yuswinda (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Nahdlatul Ulama Kalimantan Selatan, 2025)
The comfort and quality of inpatient rooms strongly influence patient recovery, especially when these spaces are designed using healing environment principles and sustainable architecture in multi-story hospitals in humid tropical climates. The study evaluates the environmental performance of three inpatient rooms at Ulin Regional Hospital in Banjarmasin by analyzing architectural design, measuring Air Changes per Hour (ACH) and illuminance (lux), and comparing the results with national standards such as Ministry of Health regulations, Indonesian National Standards (SNI), and building codes. A descriptive–evaluative mixed-method approach is applied, combining literature review, on-site observations, site and spatial analysis, and technical measurements of ventilation and lighting. The findings show that the Tulip III and Wijaya Kusuma rooms achieve ACH values above the minimum standard for inpatient wards, while measured lighting levels meet or exceed the SNI 6197:2011 requirements for visual comfort. The north–south building orientation, building depth of less than 18 meters, large window openings, and existing vegetation all help improve daylight distribution, air quality, and visual connection to natural elements, although further optimization of green spaces and therapeutic landscape quality is still needed. Overall, the research proposes an evidence-based evaluation model for inpatient rooms that integrates technical performance, healing environment concepts, and regulatory compliance, offering a useful reference for designing sustainable tropical hospitals in Indonesia